2018
DOI: 10.1080/02656736.2018.1423708
|View full text |Cite
|
Sign up to set email alerts
|

Residual tumour less than 0.25 centimetres and positive lymph nodes are risk factors for early relapse in recurrent ovarian peritoneal carcinomatosis treated with cytoreductive surgery, HIPEC and systemic chemotherapy

Abstract: The combination of both (CC1 and positive lymph nodes) makes that the indication of CRS and HIPEC should be individualised. However, the major morbidity, stage IV and the time to the adjuvant treatment were not associated with an early recurrence, so that, a major aggressiveness is recommended to achieve a CC0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Completeness of Cytoreduction Score is considered in literature an important prognosis factor. In our study, patients in which optimal resection was obtained, CC0, presented a protective factor for recurrence and decease, while CC1 proved to be a statistically significant risk factor for relapse, these results being in accordance to other published studies, which reported that the completeness of cancer resection is an independent predictor of the favorable prognosis [20]. Chemotherapy aspects are extremely important in CRS and HIPEC procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Completeness of Cytoreduction Score is considered in literature an important prognosis factor. In our study, patients in which optimal resection was obtained, CC0, presented a protective factor for recurrence and decease, while CC1 proved to be a statistically significant risk factor for relapse, these results being in accordance to other published studies, which reported that the completeness of cancer resection is an independent predictor of the favorable prognosis [20]. Chemotherapy aspects are extremely important in CRS and HIPEC procedures.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we used a residual disease classification (CC0/1/2/3) that is not commonly used to describe ovarian cancer debulking surgery but that is becoming standard practice in surgical oncology. It is classified by more discrete variables that aim to improve the precision of residual disease status reporting and has been used in other ovarian cancer survival analysis studies [33]. The satisfactory survival rates that were established in both the LGSOC and HGSOC patients who underwent a complete surgical cytoreduction (CC 0-1) in our study is in contrast with the poor prognosis of those patients who underwent an incomplete cytoreduction (CC ≥ 2).…”
Section: Discussionmentioning
confidence: 74%
“…In two recent meta-analyses (101,102 ) including observational studies and the only RCT on rEOC, CRS + HIPEC showed a significant advantage compared to CRS alone in terms of OS and DFS (if CC-3 patients were excluded). Almost all the studies agree in affirming the completeness of the cytoreduction (CC-0) as the major prognostic factor on OS and DFS (18,34,39,42,44,52,57,69,76). The reported major morbidity and mortality for CRS + HIPEC in patients with rEOC ranges from 8.3 to 72% and from 0 to 22.2% respectively.…”
Section: Hipec With Recurrent Epithelial Ovarian Cancermentioning
confidence: 83%